1977
DOI: 10.3758/bf03199700
|View full text |Cite
|
Sign up to set email alerts
|

Spectral cues which influence monaural Localization in the horizontal plane

Abstract: An extensive series of behavioral tests was carried out to determine what region, or regions, of the sound spectrum were critical for locating sounds monaurally in the horizontal plane. Seven subjects were requested to locate narrow bands of noise centered at different frequencies, combinations of these noise bands, low-pass, high-pass, and broadband noise. As observed in an earlier study, increasing bandwidth did not necessarily lead to improved localization performance until the band became broad, including,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…As mentioned earlier, there exists a penchant to displace sounds toward the open ear when locating monaurally.3 Apparently, members of Groups A and C learned to compensate for this tendency during those 60 massed trials presented on the previous day. , The finding that performance on localizing 3.0-kHz high-pass and broadband noise did not differ from one another is consistent with previous data on monaural localization (Belendiuk & Butler, 1977). Cues for locating sounds monaurally are primarily spectral and are mainly provided by the pinna.…”
Section: Discussionsupporting
confidence: 81%
“…As mentioned earlier, there exists a penchant to displace sounds toward the open ear when locating monaurally.3 Apparently, members of Groups A and C learned to compensate for this tendency during those 60 massed trials presented on the previous day. , The finding that performance on localizing 3.0-kHz high-pass and broadband noise did not differ from one another is consistent with previous data on monaural localization (Belendiuk & Butler, 1977). Cues for locating sounds monaurally are primarily spectral and are mainly provided by the pinna.…”
Section: Discussionsupporting
confidence: 81%
“…While performance in locating sounds positioned in the vertical plane improved in an orderly fashion when stimulus bandwidth was augmented, the monaural performance data for horizontal plane localization were inconsistent. The results of a further experiment also indicated that increasing the stimulus bandwidth mayor may not lead to improved performance when listening monaurally to sounds in the horizontal plane (Belendiuk & Butler, 1977). In this latter study, bands of noise, 2.4 kHz wide and centered at 5.0, 7.4, or 9.8 kHz, were presented singly and in pairs or triplets.…”
mentioning
confidence: 78%
“…However, our ability to determine the horizontal location of a pure tone is signif icantly poorer than our ability to localize a broad-band stimulus like a click [Treherne, 1985]. Moreover, we can localize sound, albeit with less accuracy, in the ab sence of binaural cues, on the basis of in formation provided at one ear [Butler, 1969;Fisher and Fredman, 1968;Belendiuk and Butler, 1977]. We must be using additional spatial cues, and monaural in put is sufficient to provide at least some of these cues.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…Because the spectral peak of a sound must change with location in order to pro vide spatial information, our localization accuracy diminishes as the bandwidth of a sound decreases [Butler and Planert, 1976;Belendiuk and Butler, 1977;Butler and Flannery, 1980;Musicanl and Butler, 1984b;Treherne, 1985]. Since the spectral peak of a tone or narrow-band sound does not change with location, our perception of location also remains fixed [Roffler and Butler, 1968], In other words, narrowband sounds create spatial illusions; our perception of location is influenced more by the frequencies in the band than its ac tual location.…”
Section: Behavioral Evidencementioning
confidence: 99%